Autogenic dynamics of alluvial fans in endorheic basins: Outcrop examples and stratigraphic significance. Issue 3 (16th December 2013) - Ventra, Dario; Nichols, Gary J.; Mountney, Nigel
Abstract Alluvial fans are relatively simple depositional systems, due to the direct coupling of sediment sources and adjacent accumulation areas. Nonetheless, general models of alluvial‐fan evolution and stratigraphy remain elusive, due to the great sensitivity of such systems to allogenic controls and their strongly case‐specific responses. Autogenic processes intrinsic to alluvial‐fan dynamics can complicate stratigraphic architectures, with effects not easily distinguishable from those of allogenic forcing. A distinction is made here between lateral autogenic dynamics, tied to spatial sediment distribution over fan surfaces, and vertical autogenic dynamics, related to independent incision‐aggradation cycles. Autogenic mechanisms have been highlighted recently by modelling studies, but remain poorly constrained in field‐based studies. Examples are presented here from the margins of the Cenozoic Teruel and Ebro basins (Spain), where alluvial fans accumulated thick successions during phases of basin topographic closure and endorheic drainage which promoted forced aggradation. Fan successions consist of conformable architectures of stacked clastic sheets, laterally continuous and with no evidence of internal unconformities, inset architectures, fan segmentation or preserved incised channels. Continuous aggradation in these closed basins strongly inhibited 'vertical' autogenic dynamics in the form of fan head and through fan incision, due to the forced rise in geomorphic base level and the creation of positive accommodation. Furthermore, the lack of incised channels favoured widespread sediment transport and aggradation over broad fan sectors in relatively short time spans, in contrast to the typical occurrence of active lobes and abandoned fan surfaces caused by 'lateral' autogenic dynamics. Stratigraphic records of alluvial fans developed in endorheic basins are essentially complete and largely unaffected by autogenic processes. The latter characteristic implies that they can be more unambiguously interpreted in terms of allogenic forcing, because stratigraphic signatures are not complicated by the effects of complex fan autodynamics.